Allografts - Johnson, D. L. (Clinics in Sports Medicine, 2009)
Preface of the editor of this special issue of the "Clinics in sports medicine": This issue is dedicated to the use of allograft tissue in knee surgery. During the last 20 to 30 years, the use of allograft tissue has increased exponentially, particularly as it relates to the field of sports medicine and knee surgery in the athletically active. Many high school and collegiate athletes have recovered from serious knee injuries and returned to the playing field because of our ability to use allograft tissue for replacement substitutes in complex knee problems. Along with this tremendous increase in the use of allograft tissue, a number of concerning issues have been brought to the forefront for discussion as well as to stimulate future research endeavors. I have asked national leaders within the knee surgery community to assist with this issue and its discussion. The table of contents is an outstanding one. I hope you will find it as enjoyable to read and learn from as I have in serving as the guest editor with these fine contributors.